(untitled) - SETIAWAN, DANAR (LATERNE, 2014)
As one of the language skills , reading comprehension is one of four skills in language ( speaking and writing skills , listening and reading comprehension ) , to learn an important part for the students. With the reading comprehension , the students can get information and improve knowledge of science . One of our own information is given with method of reading comprehension, have a comprehensive understanding of the reading and assessing the situation , the value function and the effects of reading. The decision of an effort than the support of reading comprehension can be overcome with the medium of online learning in the learning process. The Situs used in the German learning process is the situs of www.de.islcollective.com . The situs of www.de.islcollective.com contains the support of the German material that varies with the type of material , from level A1. the support of the German material on this situs is presented in an interesting , so that the material is expected , which can attract the students to deepen German language. The formulation of the problem in this study , there is the suitability of teaching materials on the situs www.de.islcollective.com as supporting materials on reading comprehension for students of Class X Semester 1 and 2 ? . And the goals of this study is to the suitability of teaching materials on the situs de.islcollective.com as the support of the materials on reading comprehension for students of Class X Semester 1 and 2 to describe. This research is a descriptive qualitative research in . The results of this study used a situs www.de.islcollective.com on reading comprehension for students of class X in school. The data sources used in this study ; the Teks reading on the situs www.de.islcollective.com , which include a number of levels A1 are systematically and gradually packed and sequentially administered there. From these results , material that can be used as the support of reading comprehension can , amounted to 7 material for topics ( knowledge and school life ) . Material on the subject : Begrüβung , and greetings and farewell , Imagine Sportverien (Andrea Sanchez ) , Ursula Beckmann, My School, A school life. Conclusion : The Situs www.de.islcollective.com , the reading comprehension